LITERASI INFORMASI SEJAK DINI: PENGETAHUAN BARU BAGI ANAK USIA DINI - Yasir Riady (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The golden age of children aged 0 to 8 years is a phase in which children begin to know the world and will determine how it will grow, develop, live and move on through life. This step of life will take place only once in human life, as well as the growth rate of rapid growth to reach about 50 % the capacity of the human intellect has occurred when the age of 4 years, 80 % occurred when the age of 8, and 100 % when the child reaches the age of 8-18 years, means such a vulnerable age in the elementary age child development. One of the things that must be understood for the development of early childhood literacy is the ability of information that must be developed early on, it can help children to have the skills and ability to identify, locate, evaluate, organize and effectively create new knowledge, use it and communicate it in a series of problem solving at hand. This paper describes the importance of information literacy as an initial stage for the child to progress in his new knowledge, the organization of early childhood education by looking at the quality and the added ability to make information literacy prior knowledge of the child so that the child develops to become intelligent, wise and noble.